1990
DOI: 10.1080/01904169009364110
|View full text |Cite
|
Sign up to set email alerts
|

Whole fruit mineral element composition and quality of harvested ‘Delicious’ apples1

Abstract: Wellspur Delicious' apple trees received preharvest foliar sprays of CaCl 2 at rates of 0, 5.9 or 19.6 kg Ca/ha. season. Fruits of uniform size (7.65 to 8.05 cm diameter) were harvested on a single date and were allowed to ripen at 19°C or were placed in controlled atmosphere storage for five months and then allowed to ripen at 19°C. Fruit quality indices were measured at various times during ripening. The CaCl 2 sprays failed to influence fruit mineral element composition, skin color, soluble solids, titratab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
3
Order By: Relevance
“…Watkins et al 19 reported that foliar application of soluble calcium salts increases firmness and reduces bitter pit and senescent breakdown in apples. In contrast, Davenport and Peryea20 observed no effect of foliar calcium application on fruit mineral element composition or post‐harvest quality of apples. Beverly et al 21 reported that to increase calcium supply to developing fruit topical spray must be applied to the fruit surface so as to be absorbed directly.…”
Section: Discussionmentioning
confidence: 87%
“…Watkins et al 19 reported that foliar application of soluble calcium salts increases firmness and reduces bitter pit and senescent breakdown in apples. In contrast, Davenport and Peryea20 observed no effect of foliar calcium application on fruit mineral element composition or post‐harvest quality of apples. Beverly et al 21 reported that to increase calcium supply to developing fruit topical spray must be applied to the fruit surface so as to be absorbed directly.…”
Section: Discussionmentioning
confidence: 87%
“…Bramlage et al (1979) found 'McIntosh' fruit firmness at harvest increased slightly with increased flesh calcium concentration; however, the firmness of 'McIntosh' apples did not appear to be influenced by preharvest sprays of calcium or other commercially available calcium mixtures (Bramlage et al 1985). Similarly, preharvest calcium sprays did not affect the calcium content or fruit firmness of other cultivars, such as 'Wellspur Delicious' (Davenport and Peryea 1990). Peryea 1991 concluded that in some cases, preharvest calcium sprays seem to be effective only when applied very often (18 times during the growing season).…”
Section: Firmnessmentioning
confidence: 92%
“…Zaradi lažje primerjave s priporočenimi vsebnostmi za dobro skladiščenje plodov, smo podatke za plodove ob obiranju v obeh sezonah preračunali še na svežo maso plodov in spet ocenili vsebnosti kalcija v plodovih glede na normative, ki so postavljeni na enoto sveže mase plodov. Tudi v sveži masi plodov so bile količine kalcija v plodovih zadovoljive, saj so presegale najnižjo priporočeno mejo za dobro skladiščenje: 4-5 mg Ca/100 g sveže mase plodov (Davenport, 1990). Ta kriterij je bil v literaturi najpogosteje uporabljen, obstajajo pa še drugi.…”
Section: Vsebnost Kalcija V Plodovihunclassified
“…V letu 1998 učinkov na omenjeno razmerje ni bilo. Raese (1996) in Davenport (1990) sta kot kriterij za dobre skladiščne sposobnosti plodov določila razmerje K/Ca, ki je manjše od 30. V obeh sezonah so imeli kontrolni plodovi največje razmerje in so se statistično značilno razlikovali od Kalgana in Calciogreena v letu 1997 in od Caltracka v letu 1998 (preglednica 2).…”
Section: Razmerja Ca/mg K/ca (K+mg)/ca V Plodovihunclassified
See 1 more Smart Citation